(untitled) (Uzbek Scholar Journal, 2023)
This article analyzes the use of Data science in the regional economy. In addition, in this article, the author analyzed the geography of the region and the ability of human activity to bring maximum economic benefit to the general development and prosperity of the region. As a result of these analyses, he developed a number of scientific proposals and recommendations on the application of Data Science in the regional economy.